PEMBANGUNAN HUNTARA PASCA BENCANA MERAPI DI KABUPATEN SLEMAN - , Harry Priyanto Putro, M. Sani Roychansyah, S.T., M.Eng., D.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
An important issue in constructing t-shelter is on how it can be finished in relatively short time. This is crucial due to the very saddening victimsâ condition at the evacuation barrack, and the fact that it needs long time for rehabilitation and reconstruction process. This research aims in: (1) exploring the planning and implementation process of the post-Merapi disaster t-shelter in Sleman regency, and (2) identifying some factors determining the process of planning for and implementation of the post- Merapi disaster t-shelter in Sleman regency. This research used deductive method with qualitative-explorative approach to produce descriptive data on the construction process of t-shelter post- Merapi disaster in Sleman regency. Data were collected using interviews, observations, and document analysis. The unit under investigation was the communal life of temporary housing organized by government and nongovernment (ACT) with Kuwang t-shelter as the focus of the study. The study showed that government and ACT had different approaches in building t-shelter. The planning for t-shelter area set by D. I. Yogyakarta government was comprehensive and involved the general public. Meanwhile, the planning set by ACT was more likely to be strategic since t-shelter was considered answer to fulfill a comfortable housing need of disaster victims. The tshelter built by ACT could become a part of solution to meet the need of housing at the stage of emergency assistance before the government t-shelter could be inhabited. The implementation of the t-shelter project could generally be conducted through three stages: area maturation, temporary housing building construction activities, and equipping public facilities. The construction project conducted by ACT was completed earlier than that done by the government. Some factors contributing to the planning process for the t-shelter were also found: the target of the t-shelter construction, data collection, site determination, general publicâs participation and readiness. Meanwhile, some factors determining the implementation process were participation in funding, site condition, the availability of the basic commodity, and the methods of the project implementation.